2019
DOI: 10.1007/s11325-019-01846-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific change in leptin concentrations during long-term CPAP therapy

Abstract: Purpose Nasal continuous positive airway pressure (CPAP) alleviates sleepiness in patients with obstructive sleep apnoea syndrome (OSAS), but part of OSAS patients keep gaining weight. Leptin and insulin-like growth factor-1 (IGF-1) interact with energy balance, and CPAP therapy has been suggested to influence these endocrine factors. We hypothesised that leptin would decrease during long-term CPAP therapy, and weight gain would associate with OSAS severity, lower CPAP adherence, lower IGF-1, and leptin concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Therefore, hyperleptinemia and leptin resistance may play important roles in the occurrence and development of OSAS. In addition to obesity, lipid metabolism disorders, systemic inflammatory responses, and oxidative stress, leptin levels were also affected by sex differences, circadian rhythm of leptin secretion, metabolic disease, and lifestyle, among others ( 68 70 ). However, because these parameters cannot be extracted from all or at least most of the included studies, it is impossible to carry out further subgroup analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hyperleptinemia and leptin resistance may play important roles in the occurrence and development of OSAS. In addition to obesity, lipid metabolism disorders, systemic inflammatory responses, and oxidative stress, leptin levels were also affected by sex differences, circadian rhythm of leptin secretion, metabolic disease, and lifestyle, among others ( 68 70 ). However, because these parameters cannot be extracted from all or at least most of the included studies, it is impossible to carry out further subgroup analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed no difference in CPAP adherence at CPAP initiation for the first time, which is consistent with a previous study. 13 The difference in adherence at re-initiation may be related to the way men and women approach CPAP therapy. Previous studies on relapses in smoking-cessation trials reported that women were more likely than men to transition from being a former smoker to a current smoker.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin levels are higher in extreme situations where sleep time is shorter or longer [ 93 ]. Additionally, leptin levels were elevated in OSA and decreased after CPAP treatment, accompanying the increase of insulin secretion [ 94 , 95 ]. Meanwhile, leptin is significantly associated with IR in patients with moderate-to-severe OSA [ 96 ].…”
Section: Resultsmentioning
confidence: 99%